Age-Related Changes in Corneal Curvature and Shape: The Shahroud Eye Cohort Study. Issue 11 (November 2015) - Hashemi, Hassan; Asgari, Soheila; Emamian, Mohammad Hassan; Mehravaran, Shiva; Fotouhi, Akbar
Abstract : Purpose: To determine 5-year changes in corneal curvature and asphericity in a population-based cohort study of 40 to 64 year olds in Iran. Methods: This report is based on data from the first and second phases of the Shahroud Eye Cohort Study conducted in 2009 and 2014, respectively. In this report, Pentacam data from 3749 people were used. Extracted variables included the maximum and minimum simulated keratometry readings (Kmax and Kmin), the mean radius of sagittal curvature (MRSC) in the central 3- and 2-mm rings between 3 to 11 mm from the center, and the anterior and posterior asphericity in both study phases. In the analysis, repeated-measures analysis of variance was used with a significance level of 0.5. Results: During the 5-year period of this survey, Kmax and Kmin increased by 0.38 ± 1.95 diopters and 0.46 ± 1.97 diopters, respectively. According to the mean radius of sagittal curvature indices, the cornea steepened in the center up to the 5- to 7-mm ring and flattened in the periphery. The increase in anterior and posterior asphericity was 0.15 ± 0.14 and 0.09 ± 0.14, respectively (all P < 0.001). Women, compared to men, showed more change in Kmax, Kmin, and posterior asphericity (all P < 0.001), but not in anterior asphericity ( P = 0.937). Conclusions: In 40 to 64 year olds, changes are in line with maintaining a prolate ellipsoid shape of the cornea. The corneal surface undergoes greater changes in women than in men. The anterior surface changes more than the posterior.